2020
DOI: 10.1021/acsami.0c14350
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Magnetic Skyrmions on Arrays of Self-Assembled Hexagonal Nanodomes for Magnetic Recording Applications

Abstract: Magnetic skyrmions are nontrivial spin textures which resist external perturbations, being promising candidates for the next generation recording devices. Nevertheless, a major challenge in realizing skyrmion-based devices is the stabilization of ordered arrays of these spin textures under ambient conditions and zero applied field. Here, we demonstrate for the first time the formation and stabilization of magnetic skyrmions on arrays of self-assembled hexagonal nanodomes taking advantage of the intrinsic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…In these ferromagnetic materials, stripe domains usually appear as the magnetic ground state, where stabilizing the skyrmions is difficult in the absence of an external magnetic field unless external manipulation or extrinsic factors (e.g., geometrical confinement) are used to promote their formation at zero fields. [21][22][23][24] Requiring an external magnetic field in potential applications for skyrmions complicates the system and increases the energy consumption of devices. [25] Therefore, spontaneous magnetic skyrmions without external fields are critically appealing.…”
Section: Introductionmentioning
confidence: 99%
“…In these ferromagnetic materials, stripe domains usually appear as the magnetic ground state, where stabilizing the skyrmions is difficult in the absence of an external magnetic field unless external manipulation or extrinsic factors (e.g., geometrical confinement) are used to promote their formation at zero fields. [21][22][23][24] Requiring an external magnetic field in potential applications for skyrmions complicates the system and increases the energy consumption of devices. [25] Therefore, spontaneous magnetic skyrmions without external fields are critically appealing.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with 2D planar geometry, the hemispherical shell structure used in this study has an advantage in terms of choosing materials, because the present geometry structure allows for the formation of stable skyrmions without an intrinsic DMI. With the advance in the development of nanofabrication technologies, such halfspherical caps can be synthesized by depositing a few layered or multilayered films onto 2D arrays of curvedsurface dot templates (e.g., spherical polystyrene particles 41,42 and nanoporous alumina membranes 43 ). Perpendicular magnetic anisotropy in such films can also be realized using Co/Pt, Co/Ni, and Co/Pt interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Other electrical reading methods were also used to read and detect skyrmions in device applications via magnetic tunnel junction or skyrmion-induced Hall voltages 9 . In addition, it was reported that localized magnetic fields from a magnetic tip allow for direct writing and reading of isolated skyrmions 43 . With the help of advances in the development of 3D nanostructures [41][42][43] as well as high-frequency measurements 44 , thereby, the present results offer an alternative opportunity to design spintronic devices based on curved-geometry-induced skyrmion formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Тонкие многослойные пленки и сплавы вида ферромагнетик/тяжелый металл рассматриваются как перспективные носители для магнитной записи [1][2][3][4][5]. Фундаментальным " байтом" магнитной информации в таких слоях является специфическая магнитная наночастицамагнитный скирмион.…”
Section: Introductionunclassified